Homogeneous acylation of Cellulose diacetate: Towards bioplastics with tuneable thermal and water transport properties. (15th February 2019) - Boulven, Manon; Quintard, Guilhem; Cottaz, Amandine; Joly, Catherine; Charlot, Aurélia; Fleury, Etienne
Graphical abstract: Highlights: Cellulose diacetate (DS = 2.45) was homogenously acylated by using a series of aliphatic acid chloride derivatives. The impact of the structural features of the bonded substituent on the plasticization was in depth investigated. Acylating reagents composed of bulky moieties at the extremity of a soft linear chain led to an efficient plastization. The water transport properties of casted films were evaluated and were decreased by the present of apolar side groups. Abstract: In this study, we report a simple, non-degrading and efficient homogeneous acylation of cellulose diacetate (CDA) by using a large panel of commercially available acylating aliphatic moieties, differing in their structure (fatty, ramified, bulky, cycloaliphatic, aromatic, more or less spaced from the cellulose backbone), in view of generating a library of well-defined cellulose mixed esters with enhanced thermoplasticity. As reflected by a lowering of the glass temperature ( Tg ), the covalent grafting confers an improved mobility to the cellulose chains, by disrupting the initial H-bonds. In particular, it appears that the gain in free volume is tailored by the substituent structure and that acylating reagents consisting in a terminal bulky moieties spaced from CDA chains by a linear chain efficiently separate macromolecular chains without generating detrimental stiffening interactions (low Tg around 125 °C). Moreover, free-standing films easily prepared by solvent casting exhibit relevant water transport properties, which are closely dictated and tuned by the water solubility of the cellulose mixed ester.